Prospek Pengembangan Jagung Pulut Untuk Mendukung Industri Di Desa Datahu - Baruwadi, Mahludin; Halid, Amir; Taliki, Zulkipli; Gobel, Nurnafiza; Khali, Jihan A.; Chossy, Achmad; Bantilan, Rianti (Universitas Negeri Gorontalo, 2023)
Gorontalo is one of the main maize producing provinces in Indonesia. This extension aims to increase the selling value of pulut corn so that it is higher. Counseling was conducted in Tambuala Hamlet, Datahu Village, Tibawa District, Gorontalo Regency starting November 16, 2022. This counseling uses primary data, namely data collected through direct interviews with respondents and secondary data obtained from reports sourced from the datahu village office, Tibawa sub-district , Gorontalo district. The counseling participants totaled about 25 people. namely 10 MSME actors, 5 corn-pulp farmers and 10 youth youth organizations. Counseling on the creation of processed corn-pulp corn innovations was carried out by delivering counseling materials to groups of female MSME entrepreneurs and female corn-pulp farmers. Each related partner is given direction by students through counseling. The production aspect is also inseparable from how to pack properly and correctly so that the product can be marketed properly. This packaging aims to make the product look more attractive and follow the current era. This counseling also focuses on digital marketing of products that will be marketed later. Digital marketing also does not only focus on marketing product sales but how participants create advertisements on social media so that products can be known by many people